Gender Differences in Capitalization Processes and the Delinquency of Siblings in Toronto and Berlin - Hagan, John (The British journal of criminology, 2004)
The focus of this paper is on youth capitalization as it relates to gender differences in the delinquency of siblings. The study of opposite-sex siblings provides a unique opportunity to examine variation in how parental capitalization of sons and daughters is influenced by the same family unit. The structural form and function of the family changed enormously in relation to gender over the latter half of the last century, as indicated in the growing participation of mothers in the labour force of Western developed nations. We find this reflected in data that we look at from both contemporary German and Canadian school settings analyzed in this paper. We argue that the male subculture of delinquency is a residue of the former hegemony of an outmoded patriarchal power structure in both of these geopolitical settings, as well as across most family settings. In settings where mothers have unusually great power relative to fathers, there is substantial and significant evidence of daughters being less controlled than sons; however, even in settings where mothers have equal or greater occupational power than fathers, and where differences in parental control of daughters relative to sons are reduced, it is still the case that these gender differences in parental control are linked to gender differences in delinquency. Male subcultural delinquency may simply be a vestigial social trait, making male subcultural delinquents the social dinosaurs of a passing, more patriarchal era